A Decentralized Autonomous Organization sob o prisma da análise econômica do Direito: os efeitos da estrutura da DAO sobre as falhas de mercado - Schmitt, Francine (Universidade do Vale do Rio dos Sinos, 2022)
This dissertation presents the concept and forms of using the Decentralized Autonomous Organization (DAO) and analyzes the effects of its operation under the theory of market failures (transaction costs and information asymmetry) in order to help comprehend the benefits of its Implementation. The concept of blockchain (a self-executing digital/electronic database, whose archiving is divided among its participants, who also have the task of verifying the veracity of the information inserted in this network) and its purposes are explained; its evolution, which resulted in the development of smart contracts (a set of codes released on the blockchain that form an automatic programming that follows the “if/then” logic, enabling the establishment of rules that must be followed by those who participate in the transactions). Blockchain is public, distributed, immutable and decentralized and these characteristics are essential to smart contracts, which were also worked on and developed by users, becoming more complex, evolving into the technology that composes the DAO. The DAO is a system formed by a group of people who share the same goals, which is organized horizontally and does not have a central authority. As mentioned, the research presents the benefits of this programming (financial savings, time savings, greater trust among the participants) and, considering these conditions, the consequences of its adoption are studied from the perspective of the economic analysis of law and the failures of Marketplace. Through qualitative, theoretical and descriptive research (articles, books, periodicals and information available on the market), we seek to identify, in practice, whether there is a decrease in transaction costs and information asymmetry when the company chooses to use the DAO
Keywords: Decentralized Autonomous Organization; Blockchain; Smart contracts; Análise econômica do Direito; Falhas de mercado; Assimetria de informações; Custos de transação; Law and Economics; Market flaws; Information asymmetry; Transactions costs; ACCNPQ::Ciências Sociais Aplicadas::Direito